Visitor Satisfaction at Merangin Garden Tour Merangin Regency, Jambi Province - Arief Rahman Rahman; Wahyu Widia Nurnatasya (International Publisher, 2022)
The purpose of this study was to find out how the facilities at the Merangin Garden Tourism Park are, to find out how the visitor satisfaction is at the Merangin Garden Tourism Park and to find out how much influence the facilities have on visitor satisfaction at the Merangin Garden Tourism Park. The method used is quantitative research methods. The type of data used is taken from several sources of primary data and secondary data. The population in this study amounted to 10,112 people, with a sample of 100 respondents. Results The correlation coefficient value of 0.648 means that the level of closeness of the relationship between facilities and visitor satisfaction is strong. For the R square value of 0.420, which means that the Facility variable affects the visitor satisfaction variable by 42% and the remaining 58% is explained by other variables that the author did not examine. The results of the t-count (8.427>1.660) so that Ha is accepted and Ho is rejected. It can be concluded that the facilities have a positive and significant effect on visitor satisfaction. It is recommended that the owner or manager improve the facilities that are inadequate and no longer suitable for use, maintain and care for the cleanliness of the park, the existing complementary facilities should be managed properly, cared for and those that are no longer feasible use replaced with new.